2009
DOI: 10.1108/09600030910973724
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging public‐private partnerships to improve community resilience in times of disaster

Abstract: Many of today's healthcare personnel find themselves in a double-bind. The question is how to remain connected, caring and compassionate with patients, while mitigating the impact of chronic workplace stress? Mindfulness is emerging as a means to address this dilemma; it has the potential to both reduce workplace stress and boost employee resilience, while enhancing the patient experience. This article describes the development of a unique collaboration between local hospitals, primary care teams and a univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
190
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(201 citation statements)
references
References 36 publications
1
190
0
4
Order By: Relevance
“…Berger (2005) concluded that adopting a multi-systemic approach was effective, not only in dealing with individuals and families, but also in changing the mood and functioning of the community. Ager et al (2010), Kumpfer and Summerhays (2006), Landau (2007), Mertensmeyer and Fine (2000 and Ungar (2010) cite similar theoretical frameworks for assessing, initiating and sustaining change in traumatised individuals and families.At a different level, Stewart et al (2009) discuss the interrelationships between public and private organisations to support community resilience and described a model of interaction that parallels Bronfenbrenner's framework. Community resilience is embedded within its economic and social systems.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Berger (2005) concluded that adopting a multi-systemic approach was effective, not only in dealing with individuals and families, but also in changing the mood and functioning of the community. Ager et al (2010), Kumpfer and Summerhays (2006), Landau (2007), Mertensmeyer and Fine (2000 and Ungar (2010) cite similar theoretical frameworks for assessing, initiating and sustaining change in traumatised individuals and families.At a different level, Stewart et al (2009) discuss the interrelationships between public and private organisations to support community resilience and described a model of interaction that parallels Bronfenbrenner's framework. Community resilience is embedded within its economic and social systems.…”
mentioning
confidence: 99%
“…Most agree (e.g. Nelson et al 2007;Stewart et al 2009;Zhou et al 2010) that resilient communities integrate the adaptive capabilities of relevant stakeholders to manage the impacts of a disaster to create a positive trajectory of functioning and adaptation. Relevant stakeholders are private and public organisations and infrastructure and their management which might operate at local, state and federal levels (Berkes 2007).…”
mentioning
confidence: 99%
See 3 more Smart Citations